Avatar : the last airbender. Chapter 2 - DiMartino, Michael Dante; Konietzko, Bryan (Los Angeles, CA : Tokyopop, 2006)
In addition to fighting for the water tribe's safety, Aang must also fight for his own, but even with the help of his friends Katara, Sokka, and Appa, he is not sure he will be able to defeat Zuko.
At head of title: Nickelodeon.
Keywords: Magic -- Fiction; Martial arts -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Cartoons and comics